TRAVEL VLOG YOUTUBE: SOCIAL CONSTRUCTION OF TECHNOLOGY AND TRAVELING CULTURE AMONG MILLENNIALS - Atika Budhi Utami; Kencana Ariestyani Suryadi (Profetik: Jurnal Komunikasi, 2021)
Travelling has become a part of lifestyle and has been closely associated with tourism sector which is potential to generate revenue. In the past 20 years, young people have played an important role in the global tourism. Research in Indonesia in 2016 revealed that 35% or 25 million young people out of the country’s 261 million population loved travelling. According to the Indonesia’s Statistic Body (Badan Pusat Statistik), millennials are keen on travelling due to the consumption shift in the society. Our productive generation prefer spending their money on seeking experiences to buying consumptive products. Besides, the fast-changing technology facilitates travellers to document their journey in a vlog format. The vlogs can later be played and shared in the Internet through social media such as YouTube and Instagram. The research aimed to analyze the interpretation of the millennials’ experience after watching travel vlogs in YouTube, and to analyze the meanings of their experience in sharing content in YouTube and other social media platforms. We used Social Construction of Technology (SCoT) Theory with phenomenological approach to analyze the aims.  The results showed that travel vlog was a progressive way of the usage and construction of social technology. Travel vlogs have brought a significant increase in travelling culture in millennials. They would rather save money to gain travelling experience than to purchase consumptive goods. They would also prefer sharing their experiences through Instastory feature in Instagram to YouTube. Having said that, YouTube should add a simpler feature so that millennials or travel vloggers can share their travelling experiences in the channel easier.